Hydrobiological Studies of Zooplankton Lake Karateren - Ph.D. Turemuratova Gulistan Ismailovna; Ph.D. Kurbanova Alfiya Ismailovna; Kurbanov Ulugbek Ismailovich (Genius Journals, 2022)
The article presents the results of hydrobiological studies of zooplankton in Lake Karateren. Lake Karateren is the deepest reservoir of the Aral Sea region. According to its species composition and quantitative indicators of zooplankton, it is estimated as a food base for valuable fish
Keywords: Zooplankton; Reservoir; Lake; Mode